Information and disclosure in strategic trade policy - Anthony Creane; Kaz Miyagiwa (Osaka University, Institute of Social and Economic Research (ISER), 2007)
We relax the standard assumption in the strategic trade policy literature that governments possess complete information about the economy. Assuming instead that governments must obtain information from firms, we examine firms' incentive to disclose information to the governments in the Brander-Spencer setting. With quantity competition, we find firms disclosing both demand and cost information, thereby justifying the literature's omniscient-government assumption. With price competition, however, firms have no incentives to disclose demand or cost information, so governments remain uninformed. Further, with quantity competition and unknown demand, governments are caught in an informational prisoner's dilemma.
Keywords: F12; F13; 330; information; uncertainty; learning; prisoner's dilemma; strategic trade; Strategische Handelspolitik; Preiswettbewerb; Informationsverhalten; Theorie